# prove that (sinθ + cosecθ)^2 + (cosθ + secθ)^2=7+tan^2θ+cot^2θ

### 2 Answers | Add Yours

`(sintheta+cosectheta)^2+(costheta+sectheta)^2`

`=sin^2theta+cosec^2theta+2sintheta*costheta+cos^2theta+sec^2theta+2costheta*sectheta`

`= sin^2theta+cos^2theta+2+2+1+cot^2theta+1+tan^2theta`

`= 1+2+2+1+1+tan^2theta+cot^2theta`

`= 7+tan^2theta+cot^2theta`

**Sources:**

The relation `(sin x + cosec x)^2 + (cos x + sec x)^2 = 7 + tan^2 x + cot^2x` has to be proved. (` theta` has been substituted with x)

Start with the left hand side:

`(sin x + cosec x)^2 + (cos x + sec x)^2`

=> `sin^2 x + cosec^2x + 2*sin x*cosec x + cos^2x + sec^2x + 2*cos x*sec x`

=> `1 + cosec^2x + 2 + sec^2x + 2`

=> `1 + 1 + cot^2x + 2 + 1 + tan^2x + 2`

=> `7 + cot^2x + tan^2x`

**This proves that **`(sin x + cosec x)^2 + (cos x + sec x)^2 = 7 + tan^2 x + cot^2x`